Practices of Nepotism and Individualism in SMEs: A Cross Cultural Analysis (Global Journal of Management and Business Research, 2018)
This article was conceived by Dr. Ekakitie Sunny (ES) and its initial objectives were x- rayed and discussed with Egede Matteo (EM). The paper was divided into several sections and each apportioned between the two authors especially the literature review section. The introductory comments were written by ES while the relevant theories/models of entrepreneurship that support the argument were written by EM. Both authors agreed on the final conclusions drawn thereto and ES wrote the abstract and the recommendations. The paper tend to argue that though the concepts of nepotism and individualism in the twilight of the 20 th and indeed early 21 st may have negative taste in modern management theory and related discusses; they nonetheless have immense relevance in the building of competitive SMEs in Africa.
Keywords: Entrepreneurship; nepotism; individualism; family-patterned businesses; global competitiveness